Examining health equity in Nepal’s climate change and health policies through the lens of environmental justice: insights from a content analysis - Sudeepa Khanal; Rehana Shrestha; Melanie Boeckmann (Global Health Action)
Background Climate change presents a multifaceted challenge with unequal health implications, particularly for vulnerable populations with limited adaptive capacity. Socioeconomic factors are intricately linked with environmental health outcomes and environmental factors significantly exacerbate existing health inequities. Health equity as a goal of environmental justice can address these issues. Objective To examine the integration of health equity within climate change and health policy documents in Nepal. Methods Using a qualitative content analysis approach based on Schlosberg’s framework of environmental justice, we analyzed the coverage of health equity considerations in climate and health policies, assessing aspects of distribution, recognition, and participation. Results Twenty-one national-level policies, strategies, and plans/guidelines on climate change and health were analyzed. Nepal’s policy documents lack clear definitions of health equity in relation to climate change, and related terms are used inconsistently. Health vulnerability is often addressed broadly rather than specifically. Health equity-related statements from environmental justice viewpoint vary across sectors. Many documents emphasize equitable distribution of resources and benefits, with participation in decision-making processes being the least discussed. Conclusions In Nepal, lack of shared understanding of health equity across sectors hinders coordinated policy efforts. There is an urgent need to expand climate change responses to consider specific health vulnerabilities. By positioning health equity as a key element of environmental justice, this study provides a broader perspective on climate change-related health equity that could encourage collaborative action between the environment and health sectors.